2015
DOI: 10.1039/c5nj01295c
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-free Pd@pSiO2 yolk–shell nanocatalysts for selective oxidation of primary alcohols to aldehydes

Abstract: The surfactant-free Pd@pSiO2 yolk–shell nanoparticles proved to be an efficient catalyst for the oxidation of substituted benzyl alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This phenomenon has been recently observed with Pd-catalysts under similar conditions and steric hindrance was given as the reason for this lower reactivity [58,59]. Veratryl alcohol oxidation was rarely reported using Pd catalysts, even more with O 2 as oxidant [60][61][62][63][64][65]. Here, veratryl alcohol reacted similarly to vanillic alcohol with the Pd NPs suspension leading to 83% of veratraldehyde after 2 h (entry 2).…”
Section: Application To the Oxidation Of Benzyl Alcoholssupporting
confidence: 68%
“…This phenomenon has been recently observed with Pd-catalysts under similar conditions and steric hindrance was given as the reason for this lower reactivity [58,59]. Veratryl alcohol oxidation was rarely reported using Pd catalysts, even more with O 2 as oxidant [60][61][62][63][64][65]. Here, veratryl alcohol reacted similarly to vanillic alcohol with the Pd NPs suspension leading to 83% of veratraldehyde after 2 h (entry 2).…”
Section: Application To the Oxidation Of Benzyl Alcoholssupporting
confidence: 68%
“…148,179,209,216 So, the metal/silica YS NPs are discussed separately under two subclasses: (i) noble metal/ silica and (ii) magnetic metal/silica. 23,47,56,92,94,96,157,170,177,211,214,215,217,218,[220][221][222][223] Ag, 219,222,224 Cu, 219,225 Pt, 210,226 and Pd 178,213,223,227,228 are reported as cores within a hollow silica shell. Most of the researchers have studied the SPR and catalytic properties of noble metal/silica YS NPs.…”
Section: Spherical Shape Ys Npsmentioning
confidence: 99%
“…[6] To overcome the obstacles, certain model compounds including veratryl alcohol (VA) and 2-phenoxy-1-phenylethanol are employed to elaborate the selective oxidation of C α À OH in the presences of different catalysts. [7] It has been demonstrated that noble metal and bimetal nanoparticles supported on certain matrices, such as Au/Al 2 O 3 , [8] Au/CeO 2 , [9] Pd/SiO 2 , [10] Pd/PG, [11] Ru/PG, [11] Ru/Al 2 O 3, [12] Ru@zeolitic imidazolate framework-8 (ZIF-8), [13] AuPd/covalent triazine frameworks, [14] AuPd/Al 2 O 3 , [15] AuCu/Al 2 O 3 , [15][16] and AuCu/C, [16] show usually decent catalytic activities for C α À OH oxidation in lignin model compounds and even lignin. Compared to nanosized Au and Pd particles, Ru nanoparticles (NPs) and their composites usually show relatively low catalytic activities, for example, the oxidation reactions need to be conducted using organic oxidant (PhIO), [11] ionic liquid [13] or high temperature (160 °C).…”
Section: Introductionmentioning
confidence: 99%